Core microRNAs regulate neural crest delamination and condensation in the developing trigeminal ganglion - Rocío B. Marquez; Estefanía Sánchez Vásquez; Andrés M. Alonso; Yanel E. Bernardi; Emilio M. Santillan; Peter Lwigale; Luisa Cochella; Marianne E. Bronner; Pablo H. Strobl-Mazzulla (Proceedings of the National Academy of Sciences, 2025)
Cranial neural crest cells (NCCs) undergo dynamic processes during embryonic development, including delamination from the neural tube by epithelial-to-mesenchymal transition (EMT), migration to the periphery, condensation via mesenchymal-to-epithelial transition (MET), and differentiation into structures like the trigeminal ganglion. Here, we identify and characterize the function of a core set of miRNAs involved in these transitions during the formation of the trigeminal ganglion in the chick embryo. We further identify putative targets of miRNAs involved in neural crest EMT and MET. Notably, introducing MET-involved miRNAs into trunk NCCs endows these cells with the ability to condense and differentiate into neurons in vivo in a manner reminiscent of cranial rather than trunk NCCs. Our findings shed light on the intricate regulatory networks governing NCC behavior, positioning miRNAs as key regulatory elements required for migratory transitions and axial level–specific differentiation capabilities.